2004
DOI: 10.1002/pmic.200300809
|View full text |Cite
|
Sign up to set email alerts
|

ApoC‐I and ApoC‐III as potential plasmatic markers to distinguish between ischemic and hemorrhagic stroke

Abstract: Early diagnosis and immediate therapeutic interventions are crucial factors to reduce the damage extent and the risk of death. Currently, the diagnosis of stroke relies on neurological assessment of the patient and neuro-imaging techniques including computed tomography and/or magnetic resonance imaging scan. An early diagnostic marker of stroke, ideally capable to discriminate ischemic from hemorrhagic stroke would considerably improve patient acute management. Using surface-enhanced laser desorption/ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 45 publications
(24 reference statements)
4
71
1
3
Order By: Relevance
“…In 135 patients, GFAP was able to distinguish ischemic from hemorrhagic stroke with 79% sensitivity and 98% specificity within 6 hours of symptom onset [22]. In a study of 31 patients, apolipoprotein CI and apolipoprotein CIII were shown to distinguish hemorrhagic from ischemic stroke with 94% sensitivity and 87% specificity [23]. In a larger study of 1146 patients, a 4 panel marker (S100B, MMP9, D-dimer and brain natriuretic factor) was able to distinguish ischemic stroke from stroke mimics including hemorrhagic stroke with 85% sensitivity; however, specificity was only 34% [24].…”
Section: Biomarkers For the Diagnosis Of Ischemic Strokementioning
confidence: 97%
“…In 135 patients, GFAP was able to distinguish ischemic from hemorrhagic stroke with 79% sensitivity and 98% specificity within 6 hours of symptom onset [22]. In a study of 31 patients, apolipoprotein CI and apolipoprotein CIII were shown to distinguish hemorrhagic from ischemic stroke with 94% sensitivity and 87% specificity [23]. In a larger study of 1146 patients, a 4 panel marker (S100B, MMP9, D-dimer and brain natriuretic factor) was able to distinguish ischemic stroke from stroke mimics including hemorrhagic stroke with 85% sensitivity; however, specificity was only 34% [24].…”
Section: Biomarkers For the Diagnosis Of Ischemic Strokementioning
confidence: 97%
“…Using the same technique, Gerton et al [70] showed that several serum proteins in the molecular weight range of 7500-18 000 Da were able to discriminate ectopic from intrauterine pregnancies. Heart fatty acid binding protein as well as apolipoprotein C-I and C-III have been proposed as potential biological markers for the diagnosis of stroke [71,72]. Interestingly, apolipoprotein C-I and C-III appeared to be the first reported plasmatic biomarkers able to accurately distinguish between ischemic and hemorrhagic stroke within a small number of patients [72].…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…Heart fatty acid binding protein as well as apolipoprotein C-I and C-III have been proposed as potential biological markers for the diagnosis of stroke [71,72]. Interestingly, apolipoprotein C-I and C-III appeared to be the first reported plasmatic biomarkers able to accurately distinguish between ischemic and hemorrhagic stroke within a small number of patients [72]. Proteomic analysis of plasma from patients suffering from acute myocardial infarction revealed also modifications of the protein pattern different from that of patients with unstable angina [73].…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…The interested reader can refer to the companion paper [10] in the same volume. In that paper two of the masses given in Table 9, namely 4480 and 6650, were identified as being possibly an antithrombin-III (AT-III) fragment and apolipoproteinC-I (ApoC-I).…”
Section: Discussion Of Biomarkersmentioning
confidence: 99%